The Role and Legal Responsibility of Using Artificial Intelligence (AI) In Medical Sector - Hasibuan, Laura Erika (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
Artificial Intelligence has brought significant transformations to the healthcare sector, ranging from disease diagnosis, medical data management, to drugs development. While it offers efficiency and accuracy, the implementation of Artificial Intelligence also raises challenges related to legal responsibilities and regulations. In the context of legal responsibility, issues such as disease diagnosis, medical data management, and drugs development become key concern. Legal responsibility for potential harm caused by Artificial Intelligence in this sector arises from the availability of information for medical professionals as well as electronic agents that manage patient data during registration in hospitals or online healthcare services, along with healthcare provision and policy formulation. This article aims to analyze the relationship between the application of Artificial Intelligence in healthcare and the legal framework and regulations in Indonesia, such as the Electronic Information and Transactions Law No. 19 of 2016 and the Health Law No. 17 of 2023. It also offers recommendations to address potential legal gaps. The conclusion of this study emphasizes the importance of developing adaptive regulations and fostering collaboration among technology experts, healthcare professionals, and policymakers to ensure the safe, fair, and responsible implementation of Artificial Intelligence.